Performance and Security for the Internet of Things : Emerging Wireless Technologies - Shajaiah, Haya; Abdelhadi, Ahmed; Clancy, Charles (McGraw-Hill's AccessEngineering., 2021)
"A hands-on guide and mathematical approach to tackling security challenges and overall performance issues in 5G-based IoT communications. The Internet of Things (IoT) provides connectivity and data exchange anytime and anywhere among a wide variety of physical objects such as sensors, vehicles, and mobile phones. This book is a concise guide to securing wireless IoT systems at the communications level, covering wireless spectrum sharing systems, smart grid communications, machine-to-machine communications, and uplink/downlink communications for IoT applications. The methods, optimization problems, mathematical solutions, algorithms, and programming codes in the book can be applied directly or extended as countermeasures for different IoT vulnerabilities."--Publisher's description.